Primary Endovascular Repair of the Ascending Aorta. Issue 6 (November 2018) - Borrello, Bruno; Carino, Davide; Agostinelli, Andrea; Budillon, Alessandro Maria; Nicolini, Francesco
Different case series have been published demonstrating the feasibility of endovascular repair of the ascending aorta in selected patients deemed unfit for open surgery. However, the use of commercially available stent graft in the ascending aorta remains off-label, and their excessive length often prevents their deployment in the ascending aorta. Here we report a case of successful primary endovascular repair of the ascending aorta using a physician modified off-the-shelf device.